Geochemical characteristics of the modern Yellow River Delta sediments and their response to evolution of the sedimentary environment - Meng, Liwei; Wang, Longsheng; Wang, Qing; Zhao, Jiawen; Zhang, Guiye; Zhan, Chao; Liu, Xianbin; Cui, Buli; Zeng, Lin (Frontiers in Marine Science, 2024)
Introduction Sedimentary evolution and river channel changes of large river delta (e.g. Huang River, Changjiang River) in response to environmental changes have been one of the key issues in global change research. Methods This study reconstructed sedimentary environment changes in the modern Yellow River Delta (YRD), based on grain size and elemental chemical analysis of two short cores (YDC and YDG) from the southern region of the Qing 8 course delta of the modern YRD. Results The results indicated that the cores YDC and YDG sediment were dominated by silt (58.47% and 67.6%, respectively) with varied grain-size variations and poor sediment sorting. The cores YDC and YDG sediments are both predominantly composed of the major element SiO2, and have an average content of 55.53% and 58.45%, respectively. The R-mode factor analysis showed the content of chemical substances of core sediments was controlled by three factors: grain size, sedimentary provenance, and marine sedimentary dynamics. Discussion Before the diversion of the Yellow River to the Qing 8 course in 1996, the two cores sediment were mainly sources from the Yellow River, and both cores were in the delta-front sedimentary environment under weak hydrodynamic conditions. After the Yellow River was diverted to the Qing 8 course, the cores YDC and YDG experienced significant erosion under the nearshore strong waves and tides. And then the sedimentary environment of the YRD changed from siltation to erosion. The results of the study would be helps to further our understanding of the changes in sediment grain size and geochemical element characteristics in the Yellow River estuary, and reveal the evolution of its sedimentary environment.